Model Penerapan Teori Relevance dalam Analisis Drama - Adriansyah Abu Katili (Yayasan Daarul Huda Kruengmane, 2026)
This article is intended to serve as a model for drama analysis using a pragmatik approach, applying the relevance theory proposed by Sperber and Wilson. The play used as an example is Arthur Miller's